Hepatoprotective Effect of Aqueous Crude Extract of Thunbergia laurifolia Leaves against Plasmodium berghei Infected Mice - Sison, Apirit; Racharsa, Wachiraya; Muangpruan, Peerapon; Srichairatanakool, Somdet; Uthaipibull, Chairat; Somsak, Voravuth (Journal of Health Research, 2017)
Background: Hepatotoxicity induced by malaria infection is commonly a significant cause of morbidity and mortality among humans. Hence, identification of medicinal plants that have hepatoprotective activity is urgently needed. Therefore, this study aimed to evaluate the hepatoprotective effect of aqueous crude extract of Thunbergia laurifolia leaves in Plasmodium berghei infected mice. Methods: Aqueous crude extract of T. laurifolia leaves was prepared and tested for hepatoprotective effect in P. berghei infected mice. The standard 4-day suppressive test was undertaken in groups of ICR mice infected with 1x107 parasitized erythrocytes, and then orally treated with the extract at doses of 1000, 2000, and 4000 mg/kg for 4 consecutive days. Pyrimethamine (1 mg/kg) was used as positive control, and combination treatment with 4000 mg/kg of extract was also determined. All liver markers were subsequently measured including aspartate aminotransferase (AST), alanine aminotransferase (ALT), cholesterol, and albumin. Results: Hepatotoxicity was induced by malaria infection in mice as indicated by progressive increase of AST and ALT, and marked decrease of cholesterol and albumin, particularly starting on day 4 after infection. Interestingly, hepatoprotective effect was found in infected mice treated with the extract in dose-dependent manner as indicated by the similar levels of all liver markers to normal mice, and the highest activity was found at dose of 4000 mg/kg. Moreover, combination treatment of pyrimethamine and the extract is recommended. Additionally, prolonged survival time of infected mice treated with the extract was also found. No side effect of this extract was observed in normal mice. Conclusion: Aqueous crude extract of T. laurifolia leaves had a hepatoprotective effect during P. berghei infection, and can be used as combination treatment with standard antimalarial drugs.